Method for processing regenerated cellulose fiber and processed fiber
By adsorbing cellulose nanofibers on the surface of regenerated cellulose fibers, the method stabilizes dimensions and reduces shrinkage and swelling, addressing the hygroscopic issues of these fibers.
Patent Information
- Application Number
- JP2024164657
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-09-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-01-25
AI Technical Summary
Regenerated cellulose fibers exhibit significant shrinkage and swelling due to their high hygroscopicity, making them difficult to wash with water and requiring dry cleaning, which is addressed by existing methods like surface treatments with long-chain hydrocarbons or crosslinking agents.
A treatment method involving the adsorption of cellulose nanofibers (CNF) on the surface of regenerated cellulose fibers, followed by a drying step, optionally with a resin component, to stabilize fiber dimensions and reduce shrinkage.
The method effectively stabilizes the dimensions of regenerated cellulose fibers and woven or knitted fabrics, reducing shrinkage and swelling after washing, while maintaining fiber flexibility and strength.
Smart Images

Figure 2024178336000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a treatment method for dimensionally stabilizing regenerated cellulose fibers obtained by spinning regenerated cellulose, and to regenerated cellulose fibers treated by the treatment method, and woven or knitted fabrics containing regenerated cellulose fibers. [Background technology]
[0002] Regenerated cellulose fibers such as rayon, polynosic, cupra, lyocell, and acetate have a unique drape and the texture, luster, and slipperiness that are unique to cellulose filaments, and are therefore used in a wide range of applications, including women's clothing fabrics in general, stoles, linings for men's and women's clothing, as well as curtains, craft threads, cloths, bags, footwear, etc. They are also widely used for underwear, taking advantage of their heat retention and moisture absorption properties, and in recent years their use has expanded to include functional underwear, etc., taking advantage of the moisture absorption and heat generation effect that occurs when moisture is adsorbed on the fiber surface.
[0003] On the other hand, the regenerated cellulose fibers are known to have a characteristic that, due to their high hygroscopicity, they absorb water and swell when immersed in water for washing or the like, and then shrink in fiber length when dried. For this reason, textiles using regenerated cellulose fibers generally have difficulty in washing with water, and have the problem of needing to be washed by dry cleaning.
[0004] The swelling property of the regenerated cellulose fiber and the associated shrinkage of the fiber length are believed to be derived from the structure of the fiber resulting from the process of producing the regenerated cellulose fiber from the cellulose raw material. In other words, in the production of the regenerated cellulose fiber, natural cellulose raw material is dissolved in carbon disulfide or cuprammonium solution, etc., and the resulting solution is spun, etc., and it is known that the crystallinity of natural cellulose decreases during the process. Due to this, the regenerated cellulose fiber exhibits swelling property because water easily penetrates between the cellulose molecules that constitute it, and it is also believed that the cellulose molecules are rearranged in the fiber when it swells, causing shrinkage after drying.
[0005] In order to solve the above problems, various improvement measures have been proposed. For example, Patent Document 1 describes a method of suppressing damage to textiles caused by washing, etc., by providing a long-chain hydrocarbon compound on the surface of regenerated cellulose fibers, etc. Furthermore, Patent Document 2 describes a method of coating the surface of regenerated cellulose fibers, etc. with amino-modified silicone to enable washing in water. Meanwhile, Patent Document 3 describes a method of applying a specific crosslinking agent that reacts with hydroxyl groups in cellulose molecules to regenerated cellulose fibers to form a crosslinked structure between and among cellulose molecules, thereby suppressing rearrangement of cellulose molecules in the fibers and suppressing shrinkage, etc., caused by washing in water, etc. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2011-6808 A [Patent Document 2] JP 2012-1830 A [Patent Document 3] JP 2005-113333 A [Patent Document 4] JP 2008-1728 A Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention aims to provide a novel treatment method for improving the problems associated with the regenerated cellulose fibers, in particular for reducing the amount of shrinkage after washing in water in woven and knitted fabrics containing regenerated cellulose fibers, thereby stabilizing the dimensions of the fabrics. It also aims to provide regenerated cellulose fibers treated by the treatment method, and woven and knitted fabrics containing the regenerated cellulose fibers. [Means for solving the problem]
[0008] In order to solve the above problems, the present invention provides the following means. (1) A fiber having an adsorbent on the surface of a twisted yarn containing elementary fibers obtained by spinning a regenerated cellulose raw material, the adsorbent including cellulose nanofibers. (2) A fiber processing method including a cellulose nanofiber adsorption step of immersing fibers containing elementary fibers obtained by spinning a regenerated cellulose raw material in a cellulose nanofiber dispersion in which cellulose nanofibers are dispersed, thereby adsorbing an adsorbate containing cellulose nanofibers, and a drying step of drying the fibers having the adsorbate containing cellulose nanofibers adsorbed thereon. The present invention further includes the following means. (3) The above fiber, in which the weight percentage of cellulose nanofiber is 0.01 wt% or more. (4) The above fiber, wherein the adsorbent further comprises a resin. (5) Woven or knitted fabrics containing the above fibers. (6) The above processing method, wherein the cellulose nanofiber dispersion contains a resin component. (7) The above treatment method further comprising a resin adsorption step of immersing the regenerated cellulose fibers in a solution containing a resin component after the drying step. (8) The above-mentioned processing method in which the above-mentioned fibers are processed into woven or knitted fabrics. Effect of the Invention
[0009] According to the present invention, the dimensions of regenerated cellulose fibers can be stabilized, and the amount of shrinkage of regenerated cellulose fibers and woven or knitted fabrics containing regenerated cellulose fibers after washing in water can be reduced. [Brief description of the drawings]
[0010] [Figure 1A] This is a photograph showing an example of the state of CNF precipitated from a CNF dispersion. [Figure 1B] This is a photograph showing an example of the state of CNF precipitated from a CNF dispersion after shrinkage prevention treatment of regenerated cellulose fibers. [Figure 2A] This is an SEM image of cupra fiber with adsorbed CNF. [Figure 2B] This is an SEM image of cupra fiber. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention is preferably applied to fibers called regenerated cellulose fibers. In the present invention, regenerated cellulose refers to cellulose and cellulose derivatives that exhibit higher hygroscopicity than natural cellulose, and includes hydrated cellulose (cellulose II) obtained by dissolving natural cellulose (cellulose I) in a specific solvent such as carbon disulfide or cuprammonium solution and then reprecipitating, and cellulose derivatives that have undergone a certain chemical modification during the process. In addition, regenerated cellulose also includes hydrated cellulose obtained by alkali treatment or the like, even if it does not dissolve natural cellulose.
[0012] Examples of the regenerated cellulose include rayon, polynosic, cupra, lyocell, fortisan, mercerized cotton, acetate, etc. In the present invention, the regenerated cellulose fiber means an elementary fiber obtained by spinning the regenerated cellulose raw material, and a fiber obtained by twisting only the elementary fiber or by blending with fibers made of other raw materials. In the present invention, the woven or knitted fabric means a fabric-like material such as a woven fabric, knitted fabric, or nonwoven fabric, and a molded product obtained by sewing the fabric.
[0013] The present invention is widely applicable to regenerated cellulose fibers and woven and knitted fabrics containing regenerated cellulose fibers, and by carrying out the treatment according to the present invention, it is possible to suppress shrinkage of woven and knitted fabrics during washing in water, etc., and also to suppress the occurrence of "grain" in the woven and knitted fabrics due to partial shrinkage of the regenerated cellulose fibers, etc. In this specification, when "regenerated cellulose fibers, etc." is mentioned, it means the above-mentioned regenerated cellulose fibers as well as woven and knitted fabrics containing the regenerated cellulose fibers.
[0014] Among regenerated cellulose fibers, particularly those containing 1 wt% or more of regenerated cellulose components relative to the total fiber weight, treatment with the shrink-proofing method of the present invention can produce effective effects. Also, for regenerated cellulose fibers containing 10 wt% or more, 30 wt% or more, or 50 wt% or more of regenerated cellulose components, or fibers or woven or knitted fabrics containing 70 wt% or more or 90 wt% or more of regenerated cellulose components and thus substantially composed of regenerated cellulose, treatment with the treatment method of the present invention reduces swelling of the regenerated cellulose fibers when they are moistened by washing in water, etc., and can effectively reduce shrinkage when they are subsequently dried.
[0015] The regenerated cellulose fibers and woven and knitted fabrics containing the regenerated cellulose fibers of the present invention are characterized in that an adsorbent containing cellulose nanofibers (hereinafter sometimes referred to as "CNF") is adsorbed on the fiber surface.
[0016] The above-mentioned CNF is a general term for fine cellulose fibers extracted by various processing methods from cellulose microfibrils, which are bundles of highly crystalline cellulose molecules contained in plant cell walls and the like (see, for example, Patent Document 4, etc.). CNF typically has an average fiber diameter of about 2 to 150 nm and an aspect ratio (fiber length / fiber diameter) of about 100 to 10,000, and is a very fine fibrous substance even compared to the elementary fibers of regenerated cellulose (diameter of about 10 μm), and is a tough fibrous cellulose whose strength per unit cross-sectional area is said to be greater than that of steel.
[0017] The mechanism by which the regenerated cellulose fibers according to the present invention have improved dimensional stability compared to untreated regenerated cellulose fibers is not necessarily clear. On the other hand, as shown in the examples, in the regenerated cellulose fibers treated by the shrink-proofing method according to the present invention, it is observed that fine fibrous CNFs or aggregates of CNFs in which the CNFs are aggregated in a fibrous form are adsorbed to the regenerated cellulose fibers. From this, it is presumed that the tough CNFs physically restrain the regenerated cellulose fibers by entangling and adsorbing them, and when the regenerated cellulose fibers absorb water and swell, the increase in the fiber diameter is inhibited, resulting in improved swelling resistance. It is also considered that the physical restraint by the CNFs prevents the rearrangement of cellulose molecules in the regenerated cellulose fibers, thereby suppressing shrinkage after drying.
[0018] The CNF used in the present invention can be used without any particular restrictions, regardless of the method for producing the CNF when obtaining the CNF from a cellulose raw material, as long as it is dispersible in a dispersion medium such as an aqueous solution. For example, CNF produced by mechanically defibrating cellulose fibers, CNF produced by acid hydrolysis or alkali treatment of cellulose fibers, and commercially available CNF in the form of a powder or aqueous dispersion, etc., can be used as the treatment liquid, and a dispersion containing the CNF at an appropriate concentration can be used.
[0019] It is believed that the CNF adsorbed to the regenerated cellulose fiber by the shrink-proofing treatment method according to the present invention suppresses the swelling of the regenerated cellulose fiber by restricting the volume increase due to water absorption of the regenerated cellulose fiber, and the effect according to the present invention can be obtained even by adsorbing a small amount of CNF to the regenerated cellulose fiber. On the other hand, by adsorbing and covering the surface of the fiber with 0.01 wt% or more of CNF based on the regenerated cellulose fiber, the interval between the CNFs on the surface of the regenerated cellulose fiber becomes small, and it becomes possible to effectively suppress the swelling when the regenerated cellulose fiber absorbs water. In addition, by adsorbing CNF at a rate of 0.05 wt% or 0.1 wt% or more to cover the fiber, it becomes possible to significantly improve the swelling property of the fiber. Furthermore, by adsorbing 0.5 wt% or 1.0 wt% or more of CNF to the regenerated cellulose fiber, it is possible to cover substantially the entire surface of the regenerated cellulose fiber with CNF.
[0020] In terms of improving the swelling properties of the fibers, there is no upper limit to the amount of CNF to be coated, but there is a tendency for the flexibility of the fibers to be lost by adsorbing and coating the regenerated cellulose fibers with an excessive amount of CNF, resulting in a so-called "paper-like" effect. Therefore, in order to maintain the texture of the regenerated cellulose fibers that are coated with CNF, it is desirable to keep the amount of adsorbed CNF below 5 wt% based on the fibers.
[0021] Considering that the diameter of the basic fiber of the commonly used regenerated cellulose fiber is about 10 μm, for example, when the fiber is coated with about 0.1 wt% CNF, the average thickness of the coating layer of the CNF is estimated to be about 2.5 nm. Since this value is less than the diameter of the commonly known CNF, it is considered that this amount of CNF does not cover the entire surface of the regenerated cellulose fiber, but is adsorbed randomly at a certain interval. In other words, the fiber surface treated by the method of the present invention does not necessarily need to be covered entirely with CNF, and it is possible to improve the swelling property by adsorbing CNF to the fiber surface at a density that can suppress the volume increase due to swelling when the fiber absorbs water.
[0022] Specifically, the swelling of regenerated cellulose fibers is improved by adsorbing and covering 10% or more of the fiber surface area with CNF, and a significant improvement in swelling can be achieved by adsorbing CNF to 30% or more or 50% or more of the fiber surface area. A significant improvement in swelling can also be achieved when the entire surface of the regenerated cellulose fiber is substantially covered with CNF, and further when the entire surface of the regenerated cellulose fiber is covered with multiple layers of CNF. The CNF adsorbed on the surface of the regenerated cellulose fiber can be observed, for example, by a scanning electron microscope, and the coverage rate of the regenerated cellulose fiber can be evaluated.
[0023] The adsorption treatment of CNF onto regenerated cellulose fibers can be carried out by a CNF adsorption step in which regenerated cellulose fibers, etc. are immersed in a CNF dispersion in which CNF is dispersed at an appropriate ratio to impregnate and adsorb the CNF into the regenerated cellulose fibers, etc., followed by a drying step in which the regenerated cellulose fibers, etc. are dried. In addition, after the drying step, the regenerated cellulose fibers, etc. are maintained in a predetermined shape and subjected to a setting treatment (shape stabilization treatment) at about 150 to 200°C, thereby giving the initial shape to the regenerated cellulose fibers, etc., with the CNF adsorbed on the surface.
[0024] The process of adsorbing CNF onto the above-mentioned regenerated cellulose fibers, etc. may involve, for example, adsorbing CNF onto single fibers of regenerated cellulose fibers before spinning, or onto regenerated cellulose fibers that have been refined or bleached, or onto a woven or knitted fabric obtained using the fibers.
[0025] Furthermore, the treatment method according to the present invention involves immersing regenerated cellulose fibers, etc. in a dispersion liquid in which CNF is dispersed to impregnate and adsorb the CNF into the regenerated cellulose fibers, etc., and is similar to the dyeing process of textile products, so it can be carried out as part of a process such as dyeing performed on textiles or woven or knitted fabrics. In other words, within the scope that does not impair the effects of the present invention, CNF may be adsorbed onto textiles or woven or knitted fabrics before or after dyeing in a dyeing process, or CNF may be mixed with a dye, etc., and adsorbed onto the regenerated cellulose fibers, etc., simultaneously with dyeing.
[0026] It is also possible to combine a process using resins that is carried out to impart various properties to regenerated cellulose fibers, etc. with the treatment using the CNF of the present invention. In other words, various combinations with processes using resins are possible, such as carrying out resin processing on regenerated cellulose fibers, etc. that have been subjected to the CNF treatment of the present invention, carrying out CNF treatment and resin processing simultaneously using a treatment liquid in which a resin component, etc. is mixed with a dispersion liquid containing CNF, and carrying out the CNF treatment of the present invention on regenerated cellulose fibers, etc. that have been subjected to resin processing.
[0027] As a means for adsorbing CNF to regenerated cellulose fibers, etc., it is possible to appropriately use, for example, a means classified as so-called dip dyeing, in which the fibers are immersed in a bath in which a dye is dissolved, and the fibers are allowed to absorb the dye, and CNF can be easily adsorbed by using a dispersion of CNF as the bath. For example, by dip dyeing high-pressure processing in which regenerated cellulose fibers, etc. are immersed in a dispersion containing CNF, sealed in a container, heated to about 120°C, and held under high temperature and high pressure, it is possible to efficiently adsorb the CNF contained in the dispersion to the regenerated cellulose fibers, etc.
[0028] In addition, in a padding processing process that is carried out as a finishing process after dyeing of a woven or knitted fabric containing regenerated cellulose fibers, the woven or knitted fabric containing regenerated cellulose fibers may be immersed in a treatment liquid containing CNF to adsorb the CNF, and then the CNF may be adsorbed onto the regenerated cellulose fibers, etc. by dehydrating with a roll, drying, heat treatment (curing) processes, etc.
[0029] In addition, CNF can be adsorbed onto the surface of regenerated cellulose fibers by simply immersing regenerated cellulose fibers in a CNF dispersion to adsorb CNF onto the surface of the fibers, and then drying or heating the fibers to produce a shrink-proofing effect. In addition, CNF can be adsorbed onto the surface of regenerated cellulose fibers by using spraying, coating, printing, etc. In addition, by performing CNF adsorption treatment on woven and knitted fabrics, particularly those containing regenerated cellulose fibers, it is expected that the CNF will be adsorbed at the intersections of fibers within the woven and knitted fabric, thereby suppressing the misalignment between fibers and providing more effective shrinkage prevention effects, etc.
[0030] In the treatment method according to the present invention, the dispersion medium for dispersing CNF can be any suitable dispersion medium within a range that does not particularly harm the regenerated cellulose fibers to be treated. As a dispersion of CNF, a CNF-containing aqueous solution in which CNF is dispersed in an aqueous solution is commercially available, and the treatment according to the present invention can be performed using a CNF aqueous dispersion obtained by appropriately diluting the CNF-containing aqueous solution. On the other hand, it is preferable to use an organic solvent that is less aggressive to regenerated cellulose fibers, such as that used in general dry cleaning, and to perform the treatment according to the present invention using a dispersion in which CNF is dispersed in the solvent, in order to prevent swelling of regenerated cellulose fibers due to water absorption that occurs during the treatment.
[0031] In the treatment method according to the present invention, it is desirable to determine the amount (concentration) of CNF in the CNF dispersion used, taking into consideration the amount of CNF adsorbed onto regenerated cellulose fibers or the like after treatment. When CNF is adsorbed onto regenerated cellulose fibers, etc. by the above-mentioned dip dyeing process, it is possible to adsorb almost all of the CNF in the CNF dispersion onto the regenerated cellulose fibers, etc., so a treatment solution can be used in which CNF is dispersed in an amount corresponding to the amount of regenerated cellulose fibers, etc. to be treated and the target amount of CNF adsorption.
[0032] In addition, when regenerated cellulose fibers, etc. are immersed in a treatment solution containing CNF under specified conditions and then dehydrated to adsorb CNF onto the regenerated cellulose fibers, etc. by a padding process, etc., it is desirable to determine the CNF concentration in the treatment solution, etc. so that the desired amount of CNF is adsorbed onto the regenerated cellulose fibers, etc. after treatment. For example, by immersing regenerated cellulose fibers in a treatment solution containing approximately 0.001% or more CNF, or by padding the fibers using the treatment solution, it is possible to reduce the swelling properties of the regenerated cellulose fibers and reduce the amount of shrinkage after washing in water.
[0033] By immersing regenerated cellulose fibers in a dispersion liquid in which CNF is dispersed, the CNF or its fibrous aggregates that come into contact with the regenerated cellulose fibers are entangled and attached to the surface of the fibers, and it is believed that the CNF is well adsorbed to the surface of the regenerated cellulose fibers, mainly because the two have the same molecular structure. It is presumed that the adsorption of the strong CNF suppresses subsequent morphological changes due to swelling of the regenerated cellulose fibers, and as a result, shrinkage when washed in water is suppressed.
[0034] In the shrink-proofing treatment of regenerated cellulose fibers, etc. according to the present invention, it is possible to further coat the regenerated cellulose fibers, etc., to which CNF has been adsorbed, with an appropriate resin component depending on the purpose of imparting a desired texture to the regenerated cellulose fibers, etc., imparting water repellency, etc. It is also possible to coat the regenerated cellulose fibers, etc., with CNF that has been mixed with a resin component, etc. in advance. In particular, by coating with a resin component, etc. in addition to adsorbing CNF, the tear strength of woven and knitted fabrics containing regenerated cellulose fibers can be improved.
[0035] Resin components used as above, mainly intended to hydrophobize the surface of regenerated cellulose fibers, include fluorine-based, paraffin wax-based, etc. In addition, the use of glyoxal resin, which is generally used for the purpose of wrinkle and shrink resistance of cellulose fibers, is expected to cause a crosslinking reaction between cellulose molecules contained in the fibers and CNF, which is preferable in terms of further enhancing the effect of the CNF treatment according to the present invention.
[0036] The CNF dispersion in which regenerated cellulose fibers, etc. are soaked for the purpose of adsorbing CNF can be mixed with appropriate chemicals, etc., depending on the purpose, such as facilitating the adsorption process by CNF. For example, various dispersants can be used for the purpose of dispersing CNF well in the CNF dispersion. Examples of dispersants include various polymers that function as surfactants, orange oil, etc.
[0037] In addition, in the CNF dispersion, it is effective to adjust the acidity according to the type of fiber to be modified, etc., in order to promote adhesion of CNF to regenerated cellulose fibers. Chemicals used to adjust the acidity include sodium hydroxide and soda ash for alkalizing, and oxalic acid, acetic acid, malic acid, etc. for acidifying. The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples. EXAMPLES
[0038] [Example 1] A fabric made of cupra (44T / 24F 2330T / M) was treated in the following manner to adsorb CNF onto the fiber surface that makes up the fabric. The adsorption treatment of the fiber surface with CNF was carried out by adding a dispersant (Meisei Chemical Industry, Alcosol GL) in an amount equivalent to 2 wt% of stock solution 1 to a CNF-containing aqueous solution (Leocrysta I-2SP, CNF content: 2.2 wt%; hereinafter sometimes referred to as "stock solution 1") manufactured by Daiichi Kogyo Seiyaku Co., Ltd., and then diluting the solution with industrial water so that the weight of the CNF solid content contained in the treatment solution (300 ml) used for each treatment was the amount shown in Table 1. As explained below, 10 g of fabric was immersed in each treatment solution, so the weight ratio of CNF to fabric in each example is the value shown in the right column of Table 1.
[0039] The treatment was carried out by immersing the fabric (10 g) in each treatment solution (300 ml) in a sealed metal container, heating it to 120°C, and holding it there for 30 minutes (high pressure dip dyeing process). It is believed that the fabric was kept at a pressure of about 2 atmospheres during the treatment. For "Comparative Example 1" in Table 1, the fabric was similarly held at 120°C for 30 minutes, except that industrial water was used. Each fabric that had been treated as described above was then dried indoors and set in a shaped state with hot air at 170°C for about 60 seconds (shape stabilization treatment), and used in the following evaluations.
[0040] [Table 1]
[0041] In the above-mentioned high-pressure dyeing process, the following evaluation was carried out to confirm the adsorption of the CNF contained in the treatment liquid when it is adsorbed onto the fiber surface. A treatment liquid (900 ml) similar to the treatment liquid used in the above-mentioned Example 1-4 was prepared, and electrolysis was carried out at 14 V for 30 minutes to precipitate the CNF dispersed and dissolved in the treatment liquid. In addition, electrolysis was carried out in the same manner on the treatment liquid (900 ml) after the adsorption treatment of the fabric corresponding to the above-mentioned Example 1-4, to precipitate the CNF remaining in the treatment liquid.
[0042] Photographs showing the state of CNF precipitated from the treatment solution before and after the above treatment are shown in Figures 1A and B. As shown in Figures 1A and B, the amount of CNF remaining in the treatment solution after use (Figure 1B) is small compared to the amount of CNF before treatment (Figure 1A), indicating that the treatment described above removes most of the CNF contained in the treatment solution by adsorption to the fabric, etc.
[0043] 2A and 2B show SEM images of the fiber surface of the fabric before and after the above treatment (Examples 1-4). As shown in FIG. 2B, the fiber surface of the fabric treated in water containing no CNF was observed to maintain the unique surface properties formed when the cupra fiber was spun. On the other hand, as shown in FIG. 2A, the fiber surface of the fabric treated in a treatment solution containing CNF was observed to have properties different from the surface properties of the cupra fiber.
[0044] The surface properties of the fiber treated in the treatment solution containing the CNF were understood to be that the CNF contained in the treatment solution was randomly adsorbed and integrated onto the surface of the cupra fiber, forming a network-like coating on the surface of the cupra fiber. Also, the streaks observed parallel to the fiber were presumed to be wrinkles that occurred when the fiber with CNF adsorbed thereon dried and contracted in volume while wet, resulting in the surface with CNF adsorbed being unable to follow the interior of the fiber.
[0045] Considering that both cupra and CNF have the same density, mainly composed of cellulose, for example, when 0.1 to 0.5 wt% of CNF is uniformly adsorbed to cupra, the radius of the cupra fiber increases by about 0.05 to 0.25%, and this increase corresponds to the average thickness of the CNF layer on the surface of the cupra fiber. The average thickness of the CNF layer when 0.1 to 0.5 wt% of CNF is attached to a cupra fiber with a radius of about 5 μm as shown in Figures 2A and B is estimated to be about 2.5 to 12.5 nm. On the other hand, since the estimated average thickness corresponds to the diameter of the CNF used (about 3 to 10 nm), it is inferred that the above amount of CNF is not uniformly adsorbed on the surface of the regenerated cellulose fiber to form a film, but is adsorbed at a predetermined interval on the surface of the regenerated cellulose fiber. In other words, in order to obtain the effects produced by adsorbing CNF onto the surface of regenerated cellulose fibers as described below, it is not necessary for the CNF to be adsorbed onto the fiber surface without any gaps to form a film. It is believed that by adsorbing CNF to the extent that it covers part of the fiber surface, it is possible to reduce the degree of fiber swelling and subsequent shrinkage during drying.
[0046] Each of the fabrics treated with the above CNF was immersed in water to wet it, using the method described below, and the degree of shrinkage that occurred during the subsequent drying process was evaluated. For the evaluation, each fabric was marked (at two locations) at 10 cm intervals, and then immersed in industrial water at room temperature for about 12 hours to fully absorb water, after which the distance between the markings was measured to evaluate the dimensional change when wet. Next, each fabric was naturally dried indoors, and the distance between the markings after drying was measured to evaluate the dimensional change after drying.
[0047] Table 2 shows the results of the evaluation. In Table 2, the shrinkage when wet and the shrinkage after drying are each a percentage obtained by dividing the distance between the markings when wet and after drying by 10 cm, with "+" indicating expansion and "-" indicating shrinkage. As shown in Table 2, it was observed that the degree of expansion that occurred when each of the fabrics that were CNF-treated as described above was lower when wetted compared with the fabric that was not CNF-treated (Comparative Example 1). In addition, in terms of the dimensional change after drying after wetting, a clear dimensional reduction was observed in the fabric that was not CNF-treated (Comparative Example 1), whereas no substantial dimensional change was observed in the fabric that was CNF-treated according to the present invention.
[0048] [Table 2]
[0049] The difference in the swelling behavior of cupra fiber with or without the above-mentioned CNF treatment was evaluated using the method described below. The evaluation was performed by measuring the cupra fiber diameter in a dry state and after immersing in water for 6 hours for the one without CNF treatment (Comparative Example 1) and the one with CNF treatment (Examples 1-4) using a polarizing microscope (Nikon ECLIPSE LOV100N POL. Transmitted observation under crossed Nicols.).
[0050] The results of the evaluation are shown in Table 3. As shown in Table 3, in the fabric not subjected to CNF treatment (Comparative Example 1), swelling due to water absorption occurred until the cross-sectional area of the fiber reached about 150%, whereas in the fabrics subjected to CNF treatment according to the present invention (Examples 1-4), the degree of swelling was suppressed to about 120%. As shown in Table 3, the reason why the degree of fiber swelling is suppressed by CNF treatment is that the fibers are restrained by the tough CNF entangled on the fiber surface, making it difficult for the fibers to expand beyond a certain level due to water absorption.
[0051] [Table 3]
[0052] The tear strength of each of the fabrics treated with the above CNF was measured in a dry and wet state according to JIS L 1096 D method (pendulum method). The tear strength measurement results are shown in Table 4. As shown in Table 4, no substantial change in tear strength was observed in the fabrics treated with the above CNF either in a dry state or in a wet state.
[0053] [Table 4] [Example 2]
[0054] A fabric made of cupra (84T / 90F 1630T / M) was treated to adsorb CNF onto the fiber surface that makes up the fabric using the following method. For the adsorption treatment of the fiber surface with CNF, a dispersant (Alkosol GL, manufactured by Meisei Chemical Industry Co., Ltd.) was added to a CNF-containing aqueous solution manufactured by Nippon Paper Industries Co., Ltd. (Cellenpia; CNF content: 1.0 wt%; sometimes referred to as "stock solution 2") in an amount equivalent to 2 wt% of stock solution 2, and then the solution was diluted with industrial water so that the weight ratio of the CNF solid content met the conditions shown in Table 5. For "Comparative Example 2" in Table 5, industrial water was used as the treatment solution.
[0055] The treatment involved immersing the above fabrics in each treatment solution using a padding treatment device, squeezing them with a roll so that the wet pick-up was 100% by weight, drying them, and then setting them with hot air at 170°C for approximately 60 seconds (shape stabilization treatment), and then using them for the following evaluations.
[0056] [Table 5]
[0057] Each of the fabrics treated with the CNF was immersed in water to wet it, and then the degree of shrinkage during drying was evaluated in the same manner as in Example 1. Table 6 shows the results of the evaluation. As shown in Table 6, in Comparative Example 2, the expansion when wet and the shrinkage after drying were significant, whereas in Examples 2-1 to 2-5 in which the treatment using CNF was performed, the dimensional change was observed to be suppressed.
[0058] [Table 6]
[0059] As in Example 1, the difference in swelling behavior of cupra fiber with or without treatment using the above-mentioned CNF was evaluated. The results of the evaluation are shown in Table 7. As shown in Table 7, in the fabric not treated with CNF (Comparative Example 2), swelling due to water absorption occurred until the cross-sectional area of the fiber reached about 170%, whereas in the fabric treated with CNF according to the present invention (Examples 2-5), the degree of swelling was suppressed to about 116%.
[0060] [Table 7]
[0061] For each of the fabrics treated with the CNF, the tear strength was measured in a dry state and in a wet state in the same manner as in Example 1. The tear strength measurement results are shown in Table 8. As shown in Table 8, no substantial change in tear strength was observed in the fabrics treated with the CNF either in a dry state or in a wet state.
[0062] [Table 8] [Example 3]
[0063] Using the following method, a fabric (polyester ratio is about 35%) made of Bemberg (120 denier) with a checkered pattern woven vertically and horizontally with polyester yarn (100 denier) was treated by coating the fiber surface of the fabric with CNF that had been mixed with a resin component in advance. Bemberg is a regenerated cellulose fiber that tends to shrink when washed in water, whereas polyester is a synthetic fiber that does not substantially shrink when washed in water.
[0064] The treatment liquid used was the stock solution 2 used in Example 2 as a CNF source, and glyoxal resin (DIC Corporation, Beckamin N-80) and the same (DIC Corporation, Beckamin M-3) as resin components, a catalyst (DIC Corporation, Catalyst 376), and a dispersant (Meisei Chemical Industry, Petrox P-200) mixed with industrial water in the ratios shown in Table 9. The above fabric was immersed in the treatment liquid using a padding treatment device, squeezed with a roll so that the wet pickup was 100% by weight, then dried, and set in a shaped state with hot air at 170 ° C for about 60 seconds and used for evaluation. The evaluation was performed by performing a hand washing test at 40 ° C and boiling (boil test) at 100 ° C for 10 minutes for the treated fabric and an untreated fabric, respectively, and then drying to evaluate the shrinkage rate.
[0065] [Table 9]
[0066] Table 10 shows the shrinkage rates after the hand washing test and the boiling test. The shrinkage rates were calculated by measuring the distance between markings that were placed at intervals of 10 cm in advance. As shown in Table 10, the untreated fabric shrunk by about 5% after hand washing and about 10% after the boiling test, whereas the shrinkage was significantly suppressed in the CNF-treated fabric. In the untreated fabric with a high shrinkage rate, it was observed that the polyester yarn, which does not substantially shrink, rose from the fabric, causing embossing.
[0067] [Table 10] [Example 4]
[0068] The tear strength of a fabric made of cupra (warp: 56T / 60 2000S, weft: 84T90 1630SZ) was examined when the fiber surface of the fabric was treated with the following CNF and when it was further treated with resin.
[0069] CNF adsorption treatment: Under the same conditions as in Example 1-1, the above fabric was subjected to a high-pressure dip-dyeing process to coat it with CNF, and then it was dried and set with hot air at 170°C for approximately 60 seconds (Example 4-1). Resin processing: The fabric (Example 4-1) that had been subjected to the above-mentioned CNF adsorption treatment was further padded with a treatment solution containing glyoxal resin (DIC Corporation, Beckamin N-80; 1 wt%, Beckamin M-3; 1 wt%), a catalyst (DIC Corporation, Catalyst 376; 0.5 wt%), and 0.5 wt% of CNF derived from stock solution 1, and was squeezed with a roll so that the wet pick-up was 100 wt%, dried, and then subjected to the same setting treatment as above (Example 4-2).
[0070] Table 11 shows the tear strength (dry state) of Examples 4-1 and 4-2, measured in the same manner as in Example 1, in comparison with an untreated fabric (Comparative Example 4). As shown in Table 11, it was observed that the tear strength of the fabric subjected to the CNF adsorption treatment was improved by further subjecting it to resin processing.
[0071] [Table 11] [Example 5]
[0072] In order to verify the difference in effectiveness when using high-pressure dyeing processing and padding processing as a means of adsorbing CNF onto fabric (fiber) using CNF that has been mixed with a resin component in advance, a study was conducted using the method described below using a fabric (Tanaka Shokai TNK-471-A) with a warp thread of diacetate (AC:75d S800T / M), weft thread of cupra (Cu:SB 60 / -), and a blend ratio of AC70% / Cu30%.
[0073] For the high-pressure dyeing process, the stock solution 1 used in Example 1 as the CNF source was mixed with glyoxal resin (DIC Corporation, Beckamin N-80), (DIC Corporation, Beckamin M-3), and catalyst (DIC Corporation, Catalyst 376) as resin components in the ratios shown in Table 12, and industrial water was added to make 300 ml, which was used as the treatment solution. The treatment was performed by immersing the fabric (10 g) in the treatment solution (300 ml), sealing it in a metal container, heating it to 100 ° C, and holding it for 20 minutes (high-pressure dyeing process). The treated fabric was dried at room temperature, and then set with hot air at 170 ° C for 60 seconds (Example 5-1). For comparison, a sample was prepared that was treated in the same manner as above, except that industrial water was used as the treatment solution (Comparative Example 5).
[0074] [Table 12]
[0075] The padding process was carried out using the stock solution 1 used in Example 1 as the CNF source, and a treatment solution prepared by mixing glyoxal resin (Beckamine N-80, manufactured by DIC Corporation), glyoxal resin (Beckamine M-3, manufactured by DIC Corporation), and catalyst component (Catalyst 376, manufactured by DIC Corporation) with industrial water in the ratios shown in Table 13. In order to exclude the effect of the hydrothermal treatment in Example 5-1 on the fibers, the padding process was carried out on the fabric obtained in the above Comparative Example 5 as a sample (Example 5-2).
[0076] [Table 13]
[0077] Table 14 shows the results of measuring the tear strength in a dry state for the above-mentioned Examples 5-1 and 5-2 and Comparative Example 5 in the same manner as in Example 1. As shown in Table 14, in terms of the tear strength after treatment, it was shown that the effect of improving the tear strength was high when the CNF treatment was performed by padding. It was presumed that this result was due to the fact that the form of CNF adsorbed on the fiber and the state of the resin change depending on the treatment method used to cover the fiber with CNF.
[0078] [Table 14] [Industrial Applicability]
[0079] By adsorbing CNF, etc. to regenerated cellulose fibers, etc. according to the present invention, it is possible to suppress shrinkage of the regenerated cellulose fibers, etc. when washed in water, etc.
Claims
1. A fiber or method characterized in that the fiber has an adsorbent on the surface of a twisted yarn containing elementary fibers obtained by spinning a regenerated cellulose raw material, and the adsorbent includes cellulose nanofibers.
2. a cellulose nanofiber adsorption step in which fibers containing elementary fibers obtained by spinning a regenerated cellulose raw material are immersed in a cellulose nanofiber dispersion in which cellulose nanofibers are dispersed, thereby adsorbing an adsorbate containing cellulose nanofibers; A fiber or a method for treating the fiber, comprising a drying step of drying the fiber having adsorbed thereon an adsorbent containing the cellulose nanofiber.
Citation Information
Patent Citations
Modification of fiber material
JP1985139873A
Fine cellulose fiber
JP2008001728A
Method for shrink-proof treatment of animal fiber by hydrophobization treatment
JP2009001941A
Cloth
JP2011006808A
Cellulosic fabric with good washing durability
JP2012001830A
